Urgency of TRIPs Waiver in Patent Legal Protection against Covid 19 Vaccine - Putu Ayu Sriasih Wesna (University of Udayana, 2021)
The emergence of Covid 19 in December 2019 in the city of Wuhan, China which spread throughout the world caused the WHO to finally declare it a pandemic. This is in line with the emergence of new products that have intellectual property values ??related to the handling of the COVID-19 pandemic, one of which is vaccines which are very essential. Intellectual Property protection provisions can lead to monopolistic practices of knowledge by the pharmaceutical industry in developed countries. This is a form of abuse of intellectual property protection, especially patent protection by corporations that hide behind exclusive rights in intellectual property protection. Exclusive rights provide the authority to prevent other people from producing and trading products whose technology is requested for protection in an effort to keep profits in the hands of intellectual property holders. The Trade-Related Aspects of Intellectual Property Rights (TRIPS) Waiver proposal promoted by India and South Africa opened the world's eyes that the increase in COVID-19 cases, the emergence of new variants and the global vaccination gap are reminders that countries in the world must work together in dealing with pandemic. In writing this research using normative legal research methods as a characteristic of legal science is its normative nature. This research started from the existence of a norm vacuum in the TRIPS Agreement where there was no neglect of several provisions in the TRIPs.